2008
DOI: 10.1099/mic.0.2008/022525-0
|View full text |Cite
|
Sign up to set email alerts
|

Secreted aspartic proteases are not required for invasion of reconstituted human epithelia by Candida albicans

Abstract: A well-known virulence attribute of the human-pathogenic yeast Candida albicans is the secretion of aspartic proteases (Saps), which may contribute to colonization and infection of different host niches by degrading tissue barriers, destroying host defence molecules, or digesting proteins for nutrient supply. The role of individual Sap isoenzymes, which are encoded by a large gene family, for the pathogenicity of C. albicans has been investigated by assessing the virulence of mutants lacking specific SAP genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
82
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(87 citation statements)
references
References 44 publications
4
82
0
1
Order By: Relevance
“…It stands to reason that pathogens would expand gene families that mediate specific interactions with the host, but this has long been very difficult to demonstrate experimentally because of technical limitations in knocking out multigene families. C. albicans has 10 secreted aspartyl proteases (SAPs) with different expression profiles and pH optima, but conclusive evidence of a role in pathogenesis has been elusive (56)(57)(58). In C. glabrata, a compelling virulence phenotype is not observed until one deletes many members of a cell wall-associated protease family (yapsins) (59).…”
Section: Discussionmentioning
confidence: 99%
“…It stands to reason that pathogens would expand gene families that mediate specific interactions with the host, but this has long been very difficult to demonstrate experimentally because of technical limitations in knocking out multigene families. C. albicans has 10 secreted aspartyl proteases (SAPs) with different expression profiles and pH optima, but conclusive evidence of a role in pathogenesis has been elusive (56)(57)(58). In C. glabrata, a compelling virulence phenotype is not observed until one deletes many members of a cell wall-associated protease family (yapsins) (59).…”
Section: Discussionmentioning
confidence: 99%
“…Monolayer cultures of oral keratinocytes have been extensively used to examine the interaction of C. albicans with host cells [21][22][23][24][25], but such studies provide limited information because the oral mucosa is a multi-layered complex tissue and signalling between cells may be important in host defence. Recently, the increased use of the RHOE multi-layered in vitro mucosal model has enabled more complex studies to be performed.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, multi-layered organotypic three-dimensional in vitro culture systems have been developed to mimic the oral mucosa [17][18][19][20]. The reconstituted human oral epithelial (RHOE) model, which is based upon the TR146 buccal carcinoma cell line cultured on a porous polycarbonate insert, has been widely used in C. albicans infection studies [21][22][23][24][25]. More advanced, alternative tissue engineered mucosal models have since been developed that consist of oral keratinocytes cultured on a fibroblast-containing extracellular matrix [20,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the level of SAP4 expression does not correlate with the importance of this gene for invasion. As shown Lermann and Morschhäuser [40], Saps are not required for invasion of reconstituted human epithelia (RHE) by C. albicans. Moreover, Langford et al [3] observed the enhanced SAP4 expression in the single null mutants: efg1/efg1 and cph1/cph1 in Lee's medium, which suggested existence of hyphaeindependent regulation pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, of the three genes examined, SAP4 expression had minimal study in C. albicans during epithelial cells colonisation and infection [36]. Moreover, the role of Sap4/5 proteins as the epithelial activating factors was doubtful [40]. Thus, we undertook investigation on the role of SAP4 during hyphae formation and adhesion to epithelial cells.…”
Section: Introductionmentioning
confidence: 99%